2008
DOI: 10.1128/iai.01241-07
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Elicited Osteoclastogenesis in Response to Bacterial Stimulation Requires Toll-Like Receptor 2-Dependent Tumor Necrosis Factor-Alpha Production

Abstract: The receptor activator of NF-B ligand (RANKL) and the proinflammatory cytokines are believed to play important roles in osteoclastogenesis. We recently reported that the innate immune recognition receptor, Toll-like receptor 2 (TLR2), is crucial for inflammatory bone loss in response to infection by Porphyromonas gingivalis, the primary organism associated with chronic inflammatory periodontal disease. However, the contribution of macrophage-expressed TLRs to osteoclastogenesis has not been defined. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
73
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 42 publications
6
73
1
4
Order By: Relevance
“…Although many virulence factors of P. gingivalis have been proposed to contribute to periodontal bone and tissue destruction (16,17,50), we have reported that various complex lipids of P. gingivalis are readily detected in periodontal disease sites without concurrent bacterial invasion or LPS recovery (21,51). We have now determined that specific lipid classes that are relatively minor constituents of this organism are responsible for activation of TLR2 and that dihydroceramide lipids are not responsible for these TLR2-mediated biological responses.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although many virulence factors of P. gingivalis have been proposed to contribute to periodontal bone and tissue destruction (16,17,50), we have reported that various complex lipids of P. gingivalis are readily detected in periodontal disease sites without concurrent bacterial invasion or LPS recovery (21,51). We have now determined that specific lipid classes that are relatively minor constituents of this organism are responsible for activation of TLR2 and that dihydroceramide lipids are not responsible for these TLR2-mediated biological responses.…”
Section: Discussionmentioning
confidence: 88%
“…These studies reported engagement of TLR2 only in vitro in mouse cells. Recent reports have demonstrated TLR2-dependent periodontal bone loss in mice following oral infection with P. gingivalis (15,16). Most recently, cell adhesion mediated through the expression of fimbriae by P. gingivalis has been implicated in promoting of TLR2-dependent oral bone loss (17).…”
mentioning
confidence: 99%
“…P. gingivalis is a common oral bacterium that has been extensively characterized for its ability to promote gingival tissue and alveolar bone destruction. P. gingivalis LPS has been reported to use either TLR4 or TLR2 in its signaling, 19,[23][24][25] and Shapira et al reported that injecting whole killed P. gingivalis bacteria into subcutaneous chambers in SJL mice resulted in enhancement of EAE. 26 In contrast to these studies that used whole bacteria or P. gingivalis LPS, our studies focused on uniquely structured, non-LPS lipids produced by P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 is responsible for the predominantly Th2-oriented immune response observed in progressive periodontitis (4). TLR2 was associated with exacerbation of P. gingivalisinduced periodontal bone loss due to TLR2-induced TNF-α-dependent osteoclastogenesis (12).…”
Section: Discussionmentioning
confidence: 99%